2015
DOI: 10.1016/j.virol.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

The T7 ejection nanomachine components gp15–gp16 form a spiral ring complex that binds DNA and a lipid membrane

Abstract: Bacteriophage T7 initiates infection by ejecting several internal capsid proteins into the host cell; these proteins then assemble into a nanomachine that translocates the viral genome from the phage head into the cytoplasm. The ejected proteins are thought to partially unfold as they pass through the lumen of the portal and the short stubby T7 tail during their entry into the cell. In vivo, the internal proteins gp15 and gp16 assemble into a tubular structure that spans the periplasm and cytoplasmic membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…6 We observed that the mainly a-helical gp15 partially unfolds at temperatures as low as 458C with an unfolding transition point of 498C, and destabilization of gp16 is observed at 408C with a thermal transition point of 44 8C. These temperatures indicate that only small amounts of energy are required for the unfolding of both proteins.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…6 We observed that the mainly a-helical gp15 partially unfolds at temperatures as low as 458C with an unfolding transition point of 498C, and destabilization of gp16 is observed at 408C with a thermal transition point of 44 8C. These temperatures indicate that only small amounts of energy are required for the unfolding of both proteins.…”
Section: Resultsmentioning
confidence: 66%
“…We recently demonstrated that gp15 and gp16 have the propensity to regain their structure after being fully thermally unfolded. 6 Here, we extended this work and show that gp15 is chemically labile and unfolds in the presence of low concentrations of guanidine hydrochloride. We also show that the gp15-gp16 complex binding to liposomes coincides with a small but significant increase of a-helical structure.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations